Use of Azospirillum brasilense and nitrogenate fertilization in maize crop - C. H. N. Pinheiro; v. M. M. Lima; M. M. Stival; V. L. Silva (Scientific Electronic Archives, 2020)
Corn is highly demanding in nitrogen, but this is an onerous element, and it is necessary to seek greater efficiency in its use in this crop. This research aimed to analyze the development of this crop using nitrogen fertilization and inoculation of Azospirillum brasilense. The experiment was conducted in a randomized block design in a 2 x 5 factorial scheme, the first factor being the inoculation of Azospirillum and the second factor the nitrogen doses (0, 50, 100, 150 and 200 kg of N.ha-1) . The interaction between the inoculant and the nitrogen fertilization showed significance in the variables plant height and stem diameter. Correct nitrogen administration is essential for maize, and application in conjunction with the inoculation of Azospirillum significantly increases yields and may be an alternative to more environmentally and economically sustainable production.